Role of CXCL9-CXCR3 AXIS, ANA & DS-DNA ABS in Pathogenicity of SLE in Iraqi Patients - Mohammed Amer Kamil, Zahraa Hussein M.Kadr, Hazima Mossa Alabassi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Systematic Lupus erythematosus (SLE) has been described as a chronic inflammatory illness where chemokines play an important role in its pathogenesis. CXCL9 and CXCR3 are chemokines that described their crucial role in immune response in SLE patients. Aim of the study: To evaluate the serum level of CXCL9- CXCr3 , ANA, ds-DNA Abs in SLE patients without treatment and compare their level with those under treatment (hydroxychloroquin ,predeslone5-20mg ,D3) Patients collecting and Methods: 180 females with SLE and healthy, with ages ranged between 20-40 years, were involved in this investigation from Medical City (Consultant of Arthritis, Consultant of Dermatology, Lobby of Hematology and Arthritis)/ Baghdad Teaching Hospital and from Al-Imameen Al-Kazimeen Teaching Hospital from August 26 to October 18, 2021. The samples were included 120 females with SLE (60 females as an early diagnosed patients (G2) without treatment, 60 females as patients that received treatment subjects (hydroxychloroquin ,predeslone5-20mg ,D3) (G3) , while the control group included 60 healthy females (G1). Five mL of venous blood were obtained from patients and healthy females for measuring ANA, dsDNA and serum levels of CXCL9 and CXCR3 which were measured using ELISA method. Results: Our findings demonstrated a significant increases in the serum levels of CXCL9, CXCR3, ANS and dsDNA in SLE patients (with and without treatment) in comparison to control group as well as a significant difference was detected between SLE patients without treatment and patients those receiving treatment. Conclusion: Based on our findings, CXCL9 and CXCR3 chemokines may have a role in the pathogenesis of SLE as they are increased in SLE patients. In addition, serum CXCL9 levels can be used as an independent biomarker of SLE activity. Interestingly, high levels of ANA and dsDNA are considered as a diagnostic indicator of SLE disease in the patients.